The Child’s Cognitive Education with the Help of Art - Linkaitytė, Giedra; Lapėnienė, Asta (Acta Paedagogica Vilnensia, 2003)
The following search results of the opportunities of child’s cognitive education are presented in the article: theoretical analysis, the gain of cognitive experience and the models of educational influence and the generalization of the experience of art education. The ability to distinguish is based on l. Kant’s theory of the cognitive process. The ideas and models of L. Vygotsky, H. Gardner and D. A Kolb are the theoretical base of education. The methodology of the practical research grounds on the created models of two processes: the gain of experience and the education with the help of art. The results and the methodology of practical education and research could be used working with the blind and weak-eyed.